A Review of Cultivated Land Space Change - Xia, Liheng; Fan, Hongjian (International Journal of Natural Resources and Environmental Studies, 2025)
This paper comprehensively reviews the research on cultivated land space change. It elaborates on the background and significance of the research on cultivated land space change, and systematically analyzes the main research contents, including the driving factors of cultivated land space change, the methods and models for its analysis, and the impacts on the ecological environment. Through a summary and analysis of relevant research, it is found that the research on cultivated land space change has important theoretical and practical significance for ensuring food security, optimizing land use, and promoting sustainable development. Finally, the existing problems in current research are pointed out, and prospects for future research directions are put forward.